SIMULASI BEBAN LALU LINTAS JEMBATAN BENTANG 40 M DENGAN MENGGUNAKAN DATA WEIGH IN MOTION (WIM) - Mahathir Mahathir; Made Suangga (Universitas Tarumanagara, 2020)
Vehicle load measurement technology continues to develop and one of them is the weigh in motion (WIM) load measurement technology. Weigh in motion (WIM) technology allow the measurement of vehicle load when vehicles moving, which is the actual load of traffic received by road and bridge. This study aims to compare the response of the bridge to the actual load of traffic from the WIM data with the standard load of SNI 1725:2016. This study using a composite steel girder bridge span 40 m, with WIM data of the Kaligawe Bridge in Semarang. Based on the characteristic of the vehicle axle load, class 40 namely the type of two-axle truck, has the largest axle load value 18 tons with an overload percentage 80%. Whereas based on the characteristic of the vehicle amount, class 30 namely the type of two-axle car, has the largest vehicle amount of 2296. The result of the 3D analysis of the bridge structure can be concluded that the WIM traffic data at Kaligawe Bridge Semarang obtained bending moment and shear force lower than the standard load of SNI 1725:2016. The ratio value of the maximum bending moment and shear force of WIM data traffic load to standard load of SNI 1725:2016 on 40 m span bridge are 0.93 and 0.96. This shows that the actual load of WIM data traffic has a load that is smaller than the standard load of SNI 1725: 2016. Keywords: bridge; design vehicle load; Monte Carlo simulation; weight in motion ABSTRAKTeknologi pengukuran beban kendaraan terus berkembang dan salah satunya adalah teknologi pengukuran beban kendaraan bergerak weigh in motion (WIM). Teknologi weigh in motion (WIM) memungkinkan pengukuran beban kendaraan dilakukan saat kendaraan melintas, yang merupakan beban aktual lalu lintas yang diterima oleh jalan dan jembatan. Penelitian ini bertujuan membandingkan respons jembatan terhadap beban aktual lalu lintas dari data WIM dengan beban rencana Standar SNI 1725:2016. Jembatan yang diteliti adalah jembatan gelagar baja komposit bentang 40 m, dengan menggunakan data WIM Jembatan Kaligawe Semarang. Berdasarkan karakteristik beban sumbu kendaraan, golongan 40 yaitu jenis kendaraan truk dua sumbu memiliki nilai beban sumbu terbesar 18 ton dengan persentase overload sebesar 80%. Sedangkan berdasarkan karakteristik jumlah kendaraan, golongan 30 yaitu jenis kendaraan mobil dua sumbu memiliki jumlah kendaraan sebesar 2296. Hasil analisis 3D struktur jembatan dapat disimpulkan bahwa beban aktual lalu lintas data WIM Jembatan Kaligawe Semarang menghasilkan momen lentur dan gaya geser yang lebih rendah dari beban standar SNI 1725:2016. Nilai rasio momen lentur dan gaya geser maksimum beban aktual lalu lintas data WIM terhadap beban standar SNI 1725:2016 pada jembatan bentang 40 m berturut-turut adalah 0.93 dan 0.96. Hal ini menunjukan bahwa beban aktual lalu lintas data WIM memiliki beban yang lebih kecil dari beban standar SNI 1725:2016.